2019
DOI: 10.1590/01047760201925012592
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Arbuscular Mycorrhizal Fungi in Forest Ecosystems of Brazil: A Review

Abstract: Brazilian forest ecosystems carry ubiquitous and rare species of arburcular mycorrhiza fungi (AMF). The method of spore morphology underestimates AMF diversity in forest ecosystems. The AMF are not specific to host-plant but to the environments where plants grow. Ubiquitous AMF species may be a source of AMF inocula for forests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 74 publications
1
19
0
Order By: Relevance
“…The use of mycorrhizae is a viable alternative to restore dunes (Bécard et al, 2004;Asmelash et al, 2016;Assis et al, 2016), giving their ability to improve soil conditions and plant growth under unfavorable conditions (Bever, 2003;Al-Karaki, 2013;Amir et al, 2013;Winagraski et al, 2019), and it is known that AMF are highly prevalent in coastal dune plants (Sigren et al, 2014). Thus, since AMF offered a possible solution to the identified problem, it was relevant to study their possible effects on the growth of Canavalia rosea (Sw.) DC., a typical dune pioneer, which was of extreme importance in the stabilization process of dunes (Kitajima et al, 2008;Mendoza-González et al, 2014) and widely used to control soil erosion in several countries due to dense cover, root binding the substrate and the quick growth (Mendoza-González et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The use of mycorrhizae is a viable alternative to restore dunes (Bécard et al, 2004;Asmelash et al, 2016;Assis et al, 2016), giving their ability to improve soil conditions and plant growth under unfavorable conditions (Bever, 2003;Al-Karaki, 2013;Amir et al, 2013;Winagraski et al, 2019), and it is known that AMF are highly prevalent in coastal dune plants (Sigren et al, 2014). Thus, since AMF offered a possible solution to the identified problem, it was relevant to study their possible effects on the growth of Canavalia rosea (Sw.) DC., a typical dune pioneer, which was of extreme importance in the stabilization process of dunes (Kitajima et al, 2008;Mendoza-González et al, 2014) and widely used to control soil erosion in several countries due to dense cover, root binding the substrate and the quick growth (Mendoza-González et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Soil aggregate stability (expressed as weighted mean diameter) was highest in the analog agroforestry site (Table 3), probably because of the greater richness of AMF and plant species. As a result, hyphae are more abundant in the soil, contributing physically and biochemically (glomalin production) to soil aggregation (Winagraski et al, 2019). This effect was observed despite the fact that EE-GRSP levels were higher in the pasture site (Table 3).…”
Section: /7mentioning
confidence: 92%
“…Although there is no specificity between symbionts for the establishment of mycorrhizal association, environmental conditions can influence the presence of host plants and, as a consequence, alter AMF community composition. Thus, some AMF species may be ubiquitous and others rare (Winagraski et al, 2019).…”
Section: /7mentioning
confidence: 99%
See 1 more Smart Citation
“…It is essential to understand the effects of riparian forest and agricultural species on AMF populations and vice versa (BRAGHIROLLI et al, 2012). Various studies WINAGRASKI et al, 2019) have investigated the characteristics of AMF communities in different ecosystems, but controversial results were obtained. Cristo et al (2018) found that the conversion of an Atlantic forest fragment to pasture reduced AMF species richness, suggesting that deforestation affected the diversity of AMF communities.…”
Section: Introductionmentioning
confidence: 99%